Molecular patterns of subclinical and clinical rejection of kidney allograft: quantity matters - Wohlfahrtova, Mariana; Tycova, Irena; Honsova, Eva; Lodererova, Alena; Viklicky, Ondrej (Kidney & blood pressure research, 2015)
BACKGROUND/AIMS: Subclinical rejection diagnosed from protocol biopsies is thought to be a risk factor of long- term allograft dysfunction. The reason why in some patients subclinical rejection does not represent risk for progression is not fully understood. METHODS: The intragraft expression of 376 target genes involved in chemokine defense, apoptosis, inflammation, tolerance and TGF-β signalling pathways was measured using quantitative real-time RT-PCR (2(-)∆∆(Ct)) method in subclinical inflammation (SCI, n=10), clinical inflammation in acute T-cell mediated rejection (CI, n=10) and no rejection samples (n=9). RESULTS: Clinical inflammation group showed a increased expression of genes for chemotaxis mediating cytokines (CCL1, CCL17, CCL24, CCL25, CCL26), cytokine receptors (CCR1, CCRL2, IL1RAPL2, CXCR5), proinflammatory cytokines (IL12A, LTA), inflammatory mediator (PTAFR), complement protein C3, executioner protein of apoptosis (CASP7), growth factor (TGFA), colony stimulating factor (CSF-2), proteins involved in dendritic cells differentiation and interaction (CD209, LAMP3), regulation of immune response (LILRB2, LILBRB4). The quantitative difference in transcripts signature between SCI and CI is consistent with stronger proinflammatory setting of CI. Prostaglandin E2 receptor gene expression was independently associated with lower risk of further graft function deterioration (OR 0.11, CI 0.01-0.78, p<0.0001). CONCLUSION: Subclinical acute kidney inflammation has transcriptional profile of immune injury of lower extend compared to clinical acute inflammation.
Keywords: výsledek terapie; exprese genu; Receptors, Cytokine; Gene Expression; Male; Chemokines; Graft Survival; Immunosuppressive Agents; Inflammation; progrese nemoci; Transforming Growth Factor beta; mediátory zánětu; cytokiny; signální transdukce; Adult; biopsie; Aged; dospělí; mužské pohlaví; senioři; Disease Progression; Graft Rejection; Signal Transduction; transformující růstový faktor beta; zánět; Treatment Outcome; lidé; RNA; ženské pohlaví; Kidney Transplantation; transplantace ledvin; Humans; rejekce štěpu; přežívání štěpu; receptory cytokinové; apoptóza; Risk; Biopsy; Cytokines; Inflammation Mediators; Female; riziko; lidé středního věku; chemokiny; imunosupresiva; Middle Aged; Apoptosis